THE JADIDS’ LITERARY CRITICAL VIEWS IN THE PRESS - Arapjonova Zebo Otabek qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article explores the literary critical perspectives of the Jadid movement as expressed in the press. It examines how Jadid intellectuals used newspapers and magazines to challenge traditional literary forms and advocate for modernization in literature and society. The study highlights the role of the press in promoting national awakening, cultural reform, and educational progress through literary criticism. The findings demonstrate that Jadid literary criticism was instrumental in shaping modern Uzbek literature and played a significant role in the broader socio-cultural transformation of Central Asia during the early 1900s.